1991
DOI: 10.1111/j.1651-2227.1991.tb11883.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reactions to a Child's First Febrile Convulsion:A Follow‐up Investigation

Abstract: The severe psychological reactions of most parents to the first febrile convulsions of their child contrast with the doctors' consideration of febrile convulsions as a simple and benign phenomenon. Fifty-two parents whose child had been admitted with febrile convulsions were interviewed about their immediate and long-term reactions. Most of the parents knew little about febrile convulsions before the fit. Parents with previous knowledge of febrile convulsions took more appropriate measures during the fit than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 3 publications
1
52
1
2
Order By: Relevance
“…[2][3][4][5][6][7][8] In recent years, the prevention of recurrent febrile seizures has become a debatable issue; prevention may not be necessary because almost all febrile seizures are not injurious to the child. 9 -11 However, prevention of seizure recurrences serves two useful purposes: meeting parental fear of recurrent febrile seizures in general 12,13 and reducing the small risk of a long-lasting and eventually injurious recurrent seizure. 9 -11 Intermittent treatment with diazepam during fever is associated with adverse effects and has not been proven efficacious to prevent febrile seizure recurrences.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In recent years, the prevention of recurrent febrile seizures has become a debatable issue; prevention may not be necessary because almost all febrile seizures are not injurious to the child. 9 -11 However, prevention of seizure recurrences serves two useful purposes: meeting parental fear of recurrent febrile seizures in general 12,13 and reducing the small risk of a long-lasting and eventually injurious recurrent seizure. 9 -11 Intermittent treatment with diazepam during fever is associated with adverse effects and has not been proven efficacious to prevent febrile seizure recurrences.…”
mentioning
confidence: 99%
“…A study by Kayserili et al (25), revealed that 70% of the parents directly consulted a doctor without making any intervention. Similar studies found the rates of 36-90% for the same parameter (5,23,26). In a study of Flury et al (20), 42% of the parents said that they would try to reduce the fever, and 29% stated that they would safely lay the child on a flat surface.…”
Section: Discussionmentioning
confidence: 66%
“…There are a number of studies on the reactions of parents during and after FS (5,15,16). These reactions include physical, psychological and behavioral symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations